Achieving mechanically sturdy properties and high energy density for Zn-ion structural batteries based on carbon-fiber-reinforced composites. (8th February 2022) - Liu, Xu; Li, Hongmeng; Wang, Jiahui; Han, Qigang; Liu, Chunguo
Abstract: The composites structural batteries obtain more and more attention for lightweight in vehicles and aircraft, which needs the structural batteries to have outstanding mechanical properties and electrochemical performance, simultaneously. Herein, the lightweight carbon fiber reinforced Zn-ion structural battery was developed by the vacuum infusion layup process in the open-air environment. The fabricated composites structural devices exhibited a high tensile strength of 179.5 MPa and flexural strength of 229.6 MPa, suggesting the excellent stiffness of the structural battery. Furthermore, the composites Zn-ion structural battery realized a discharge specific capacity of 155 mAh g −1 at 0.1 A g −1 and a corresponding energy density of 205 Wh kg −1 . The relatively high capacity retention of 85.3% was also achieved after 300 cycles at 1 A g −1 . This work will inspire more research works to develop safe structural batteries with high energy density. Graphical abstract: Carbon-fiber-reinforced Zn-ion structural batteries achieved multifunctional performance with mechanically sturdy properties and high energy density. Image 1 Highlights: The Zn-ion structural batteries were fabricated by vacuum infusion layup process in an open-air environment. The Zn-ion structural batteries delivered high tensile strength (179.5 Mpa) and flexual strength (229.6 Mpa). The high energy density of 205 Wh kg −1 was realized by the Zn-ion structural batteries.